ASSESSMENT OF HEAVY METALS DISTRIBUTION IN THE SURFACE SEDIMENT OF KEMAMAN RIVER, TERENGGANU - B.MARAN, VISHALINI; ANTHONY DASS, DORINDA ANTHONY; RAVIKUMAR, LAVANNIA; IZYAN ZAINI, NUR SYAMIMI; SYAKIRAH ROSLI, NUR ALIAH; MIOR BAHARUDIN, WAN NUR IZWANI; MUSTAFFA, NAJAH KARIMAH; CHUAN, ONG MENG (Universiti Malaysia Terengganu Journal of Undergraduate Research, 2021)
In the present day, rivers are used by people as water sources for their daily agricultural, industrial and cleaning purposes. However, industrial development and human activities are rapidly impacting the river’s catchment area, which can cause contamination of heavy metals in the water and sediment. The Kemaman River is one of the rivers that may be affected by these pollutants. Thus, the concentration of selected heavy metals such as copper (Cu), zinc (Zn), cadmium (Cd), lead (Pb), arsenic (As) and mercury (Hg), plus the pollution status was determined in the surface sediments of the Kemaman River. A total of 46 sediment samples were collected along the river. Teflon Bomb digestion method with 2.0mL of mixed acid (concentrated nitric acid, hydrochloric acid and hydrofluoric acid with ratio 3:3:1) was performed followed by analyzation using Inductively Coupled Plasma Mass Spectrometry (ICPMS). The status of heavy metals contamination in the study area was determined by the index of geoaccumulation (Igeo) and pollution load index (PLI). The calculated Igeo value suggested that the sediments in the Kemaman River were categorized under unpolluted to polluted category. However, the calculated PLI suggested that the study area is polluted with heavy metals. The correlation of the sediment mean grain size and the selected heavy metals was strongly correlated. The concentration of metals increased with the rising mean grain size, which suggests their association with the fine fraction of the sediment.